Silicon Nutrition: A New Perspective to Improve Heavy Metal Toxicity Tolerance in Plants for Sustainable Agriculture - Faizan, Mohammad; Karabulut, Fadime; Alam, Pravej; Rajput, Vishnu D.; Sehar, Shafaque; Hayat, Shamsul (Springer, 2024)
World's population is facing serious constrains due to the deposition of heavy metals (HMs) in soil since last decades. Over the years, there has been an increased concern in relation to the HMs impact on the agricultural production. The HMs stress causes severe constrains in yield due to disruption of several physio-biochemical and metabolic activities of the plants. At present, the majority of agricultural practices still rely on conventional methods such as fertilizers and pesticides, but the implementation of more sustainable methods is necessary to meet the nutritional needs of the growing population, which is expected to reach several times higher than the present record. Recently, Si has attracted the attention of researchers for improving the plants growth and development in the presence/absence of HMs stress. In plants, Si nutrition could mitigate the HMs concentration in plants via reducing transpiration rate and improvement in enzyme activities. This review provided an overview on key step towards the toxicity adjustment and morpho-physiological detoxification of HMs by Si. In addition, the emerging role of Si nanoparticles (NPs) to mitigate the HMs toxicity is also highlighted.
Keywords: Agricultural production; Silicon nutrition; Toxicity adjustment; Metabolic activities